Rediscovery of the holotypes of Mustela africana stolzmanni Taczanowski, 1881 (Carnivora: Mustelidae) and Cuniculus taczanowskii Stolzmann, 1885 (Rodentia: Cuniculidae) at the Museum and Institute of Zoology Polish Academy of Sciences in Warsaw, Poland - Piechnik, Łukasz; Mierzwa-Szymkowiak, Dominika; Kurek, Przemysław (Zootaxa, 2017)
The turbulent history of Warsaw resulted in great losses in Polish zoological museums and archives especially during First and Second World War (Kazubski 1996; Fedorowicz & Feliksiak 2016). However, before 1939 Warsaw’s zoological collection deposited in the State Zoological Museum (now called: the Museum and Institute of Zoology Polish Academy of Sciences in Warsaw—MIZ PAS), especially the department of neotropics, used to be one of the best developed and well cataloged collections in Europe. There were also many holotypes of mammal species stored here after Polish expeditions to the neotropics. As a result of these events current bibliography and on-line databases (GBIF, VertNet) up to now did not mention the location of holotypes of collected taxa or even recognize them as missing (Ramírez-Chavez et al. 2014; Patton et al. 2015). We reviewed the collection to estimate the presence and status of the surviving descriptive types (holotypes). The aim of this study was to order our knowledge about the holotypes taking into account especially information about lost specimens and to explain the contradictory information about their status in the present. In 2015–2016 all type specimens in the MIZ PAS collection of neotropical mammals were revised. During revision relevant information from specimen labels was compared with the data provided in the original descriptions contained in publications from the end of nineteenth century (Taczanowski 1881; Thomas 1884; Stolzmann 1885; Thomas 1893; 1894). The results were compared with the collection databases of the Natural History Museum in London (http://data.nhm.ac.uk). Systematics and species nomenclature were followed by Wilson & Reeder (2005). Zoological nomenclature types were followed by International Commission on Zoological Nomenclature (ICZN). The results of the revision are presented as a systematic list.